Case of steroid-resistant Crohn's-associated bronchiolitis in the setting of quiescent gastrointestinal disease treated with infliximab. Issue 1 (28th November 2018) - Chuah, Cher Shiong; Noble, Colin; Leitch, Andrew
Abstract : A fit, 36-year-old man with a history of Crohn's disease previously treated with azathioprine, presented acutely with progressive shortness of breath on exertion and pleuritic chest pain. At the time of presentation, his Crohn's disease was quiescent, supported by a normal faecal calprotectin. The initial chest CT suggested the presence of a diffuse inflammatory disorder and he was subsequently started on high dose oral steroids. Despite 4 months of steroid therapy, there was minimal improvement. Following discussion at the inflammatory bowel disease multidisciplinary team meeting, a decision was made to commence infliximab. Subsequently, he made a dramatic clinical and physiological recovery. His forced expiratory volume in 1 s improved from 2.22 L/min (50% predicted) to 3.65 L/min (93% predicted) and he returned to baseline levels of exercise.